2014
DOI: 10.1016/j.psychres.2014.03.039
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social content and negative symptoms on affective ratings in schizophrenia

Abstract: The anhedonia paradox has been a topic of ongoing study in schizophrenia. Previous research has found that schizophrenia patients report less enjoyment from various activities when compared to their healthy counterparts; however, the two groups appear to have similar in-the-moment emotional ratings of these events (Gard et al., 2007; Herbener et al., 2007; Horan et al., 2006). This study examined these in-the-moment experiences further, by assessing whether they differed between social and non-social experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
(82 reference statements)
1
6
0
Order By: Relevance
“…To the best of our knowledge, only three other studies analysed ratings for social and nonsocial affective stimuli in patients with schizophrenia separately. Yet, while no effects of sociality on arousal ratings were found by Peterman et al (2015), a result congruent with the one observed here was reported by Bodapati and Herbener (2014) who observed that patients with schizophrenia demonstrate more blunted emotional responses to negative social stimuli compared to healthy controls. In another behavioural study the effects of the social content on the ratings of affective stimuli were compared between patients with schizophrenia, patients with…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To the best of our knowledge, only three other studies analysed ratings for social and nonsocial affective stimuli in patients with schizophrenia separately. Yet, while no effects of sociality on arousal ratings were found by Peterman et al (2015), a result congruent with the one observed here was reported by Bodapati and Herbener (2014) who observed that patients with schizophrenia demonstrate more blunted emotional responses to negative social stimuli compared to healthy controls. In another behavioural study the effects of the social content on the ratings of affective stimuli were compared between patients with schizophrenia, patients with…”
Section: Discussionsupporting
confidence: 91%
“…Both behavioural (Aminoff et al, 2011;Bodapati and Herbener, 2014) and physiological (Peterman et al, 2015) studies documented differences between patients' and controls' responses to social and nonsocial affective stimuli, thus there is a strong rationale to hypothesise discrepant neural patterns in both groups in reaction to the two types of the stimuli.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Healthy controls rated negative social stimuli as more arousing compared with negative nonsocial stimuli; but this effect was not observed in patients [28]. In a study of threat-related detection, healthy controls showed an expected threat-superiority effect (i.e.…”
Section: Social Preference and Schizophreniamentioning
confidence: 99%
“…Within this framework, visual social (i.e., human) content, such as human faces and bodies, has special status in the competition for prioritized processing. For example, faces or bodies are fixated first in naturalistic scenes (e.g., Fletcher-Watson, Findlay, Leekam, & Benson, 2008;Rosler, End, & Gamer, 2017), faces attract gaze in experimental tasks even at a cost (Cerf, Frady, & Koch, 2009), and only responses to social stimuli reflected the effects of anhedonia in people with schizophrenia compared to healthy controls (e.g., Bodapati & Herbener, 2014). However, unbalanced representation of social and nonsocial information in affective stimulus sets has limited the clear determination of effects as attributable to, or independent of, social content.…”
Section: Introductionmentioning
confidence: 99%